R for dummies - De Vries, Andrie; Meys, Joris (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
This accessible guide is the ideal introduction to R for complete beginners. Learn to master the programming language of choice among statisticians and data analysts worldwide.
Introduction -- Getting started with R programming -- Getting down to work in R -- Coding in R -- Making the data talk -- Working with graphics -- The part of tens.
Includes index.
Keywords: R (Computer program language).; Mathematical statistics -- Data processing